A contextualised review of genomic evidence for gene flow events between Papuans and Indigenous Australians in Cape York, Queensland. (30th November 2021) - Wasef, Sally; Wrobel, Gabriel; Wright, Nathan; Wright, Joanne L.; Adams, Shaun; Kariwiga, Jason; Leavesley, Matthew; Collard, Mark; Westaway, Michael C.
Abstract: It has long been accepted that the Indigenous groups of Australia's Cape York Peninsula have numerous cultural traits that were adopted from people in New Guinea and/or the Torres Strait Islands after the formation of the Torres Strait around 8000 years ago. However, opinions differ on whether the movement of the traits in question was accompanied by gene flow events. Some argue for a significant amount of gene flow resulting from voyages from New Guinea and the Torres Strait Islands down the east coast of Cape York. Others contend that there was only contact at the northern end of the Cape and that the cultural traits spread through down-the-line transmission. In recent years partnerships between Australian institutions and Indigenous communities in Cape York have led to new genetic research that provides benefits to both parties. We review the currently available genetic data that have the potential to shed light on this issue, concluding that the data are inconsistent with significant gene flow between Indigenous Australians and Papuan people between 8000 years ago and the colonial period. There are indications of gene flow, but it most likely occurred in the Pleistocene rather than the Holocene. As such, the currently available genomic data do not support the hypothesis that the diffusion of cultural traits from New Guinea and/or the Torres Strait Islands into Cape York was accompanied by gene flow. The data suggest instead that the cultural traits most probably spread via down-the-line trade, exchange, and imitation. Our review highlights the gaps in the available genomic information from contemporary and ancestral descendants of Australia's first settlers, and we suggest that researchers adopt a more collaborative approach, involving Indigenous communities and their knowledge in project design, data collection, and dissemination, in future genomic studies in Australia.